The ethics of climate change: An introduction - Willston, Byron (London Routledge, 2024)
The Ethics of Climate Change: An Introduction systematically and comprehensively examines the ethical issues surrounding arguably the greatest threat now facing humanity. This second edition has been updated and includes two new chapters on climate change and capitalism and climate change and law.
Keywords: Global environmental change Moral and ethical aspects; Environmental ethics; Climate Change aspect moral